Application of ROTEM to assess hypercoagulability in patients with lung cancer. Issue 6 (June 2015) - Davies, N.A.; Harrison, N.K.; Sabra, A.; Lawrence, M.J.; Noble, S.; Davidson, S.J.; Evans, V.J.; Morris, R.H.K.; Hawkins, K.; Williams, P.R.; Evans, P.A.
Abstract: Background: Venous thromboembolism (VTE) is common in patients with cancer, contributing significantly to morbidity and mortality Currently, no test reliably identifies patients at increased risk of developing VTE who would therefore benefit from prophylactic intervention. The aim of the current study was to evaluate rotational thromboelastometry (ROTEM) in identifying VTE risk in patients with lung cancer. We also compared parameters of ROTEM in patients with limited and extensive disease. Methods: Parameters of ROTEM were measured in 67 patients with lung cancer and 72 age-matched healthy controls and compared with conventional markers of haemostasis. Patients were followed up for 12 months and VTE incidence recorded. Results: Lung cancer patients had a reduced clotting time (CT), increased maximum clot firmness (MCF) and increased alpha angle compared with controls. Patients also had significantly higher levels of fibrinogen and PAI-1 than controls and in the former group there was a strong correlation between fibrinogen and both MCF and alpha angle. Six patients developed a VTE during the follow-up period and all had values for MCF at or above the upper limit of normal for EXTEM. Conclusions: This study demonstrates that several ROTEM parameters are significantly different in lung cancer patients compared to healthy age-matched controls, whereas only one of the parameters measured is significantly different between extensive compared to limited disease. No differences were observed between patients who developed a VTE compared to those who did not, highlighting the limitations of ROTEM use in patients with lung cancer. Highlights: ROTEM analysis was performed on 67 lung cancer patients compared to healthy controls Significant differences in ROTEM parameters were identified between the two groups No significant differences were identified between limited and extensive disease Patients who developed a VTE were not significantly different to those who had not ROTEM use cannot assess hypercoagulability in different stages of lung cancer